Interview with Stephen J. Ball: Analysing his contribution to education policy research - Marina Avelar (Arizona State University, 2016)
This interview aims to explore Stephen J. Ball's main contributions to the research field of education policy, while discussing the potentialities for researchers in different contexts of using his work, especially in Latin American countries. So firstly, we consider Ball's epistemological position, to then explore some of his main concepts and tools. This is followed by a discussion about the possibilities and limitations of transposing Ball's analytical tools and using his work in countries other than England. We then examine the limitations of the nation state as a framework in current education policy research. In doing so, we analyze some implications for education policy research of what Ball calls global education policy networks, which includes the work of new actors from business and philanthropy in education. Winding up, we consider the importance of research context in education policy research, to then finish with brief comments about education in Latin America.